Transdiagnostic, affect-focused, psychodynamic, guided self-help for depression and anxiety through the internet: study protocol for a randomised controlled trial. Issue 6 (19th December 2012) - Johansson, Robert; Hesser, Hugo; Ljótsson, Brjánn; Frederick, Ronald J; Andersson, Gerhard
Abstract : Introduction: Cognitive behaviour therapy delivered in the format of guided self-help via the internet has been found to be effective for a range of conditions, including depression and anxiety disorders. Recent results indicate that guided self-help via the internet is a promising treatment format also for psychodynamic therapy. However, to date and to our knowledge, no study has evaluated internet-delivered psychodynamic therapy as a transdiagnostic treatment. The affect-phobia model of psychopathology by McCullough et al provides a psychodynamic conceptualisation of a range of psychiatric disorders. The aim of this study will be to test the effects of a transdiagnostic guided self-help treatment based on the affect-phobia model in a sample of clients with depression and anxiety. Methods and analysis: This study will be a randomised controlled trial with a total sample size of 100 participants. The treatment group receives a 10-week, psychodynamic, guided self-help treatment based on the transdiagnostic affect-phobia model of psychopathology. The treatment consists of eight text-based treatment modules and includes therapist contact in a secure online environment. Participants in the control group receive similar online therapist support without any treatment modules. Outcome measures are the 9-item Patient Health Questionnaire Depression Scale and the 7-item Generalised Anxiety Disorder Scale (GAD-7). Process measures that concerns emotional processing and mindfulness are included. All outcome and process measures will be administered weekly via the internet and at 6-month follow-up. Discussion: This trial will add to the body of knowledge on internet-delivered psychological treatments in general and to psychodynamic treatments in particular. We also hope to provide new insights in the effectiveness and working mechanisms of psychodynamic therapy based on the affect-phobia model.